Sejmiki województwa płockiego 1780-1786 - Filipczak, Witold (Przegląd Nauk Historycznych, 2009)
The article discusses the sejmiks of Płock Voivodeship, which assembled in Raciąż between 1780 and 1786. It depicts preparations for the particular sejmiks as well as their course and results. The author shows the nuances of political and personal influences. Płock Voivodeship was dominated by the royalist party, supervised by the brother of King Stanislaw August, Michał Poniatowski, the bishop of Płock (the Archbishop of Gniezno since 1784). The voivodeship of Płock was the scene of rivalry between the Sierakowski family (the most important person being Maksymilian, podkomorzy, who later became the Castellan of Płock), the Bohkowski family, and their opponents, i.e. the Zielinski family. The latter were led by Ludwik, łowczy of Płock, who eventually became the Castellan of Rypin. The author analyses the important injunctions included in the instructions for the Sejm deputies from Płock. He also focuses on the organisation and procedures of the sejmiks in Raciąż. Finally, he discusses the parliamentary elites of Płock, i.e. the persons who started the proceedings, marshals, assessors, the sejm deputies, the judges of Crown Tribunal and candidates for local judges elected by the szlachta.